The involvement of J-protein AtDjC17 in root development in Arabidopsis - Petti, Carloalberto; Nair, Meera; DeBolt, Seth (Frontiers in Plant Science, 2014)
In a screen for root hair morphogenesis mutants in Arabidopsis thaliana L. we identified a T-DNA insertion within a type III J-protein Atdjc17 caused altered root hair development and reduced hair length. Root hairs were observed to develop from trichoblast and atrichoblast cell files in both Atdjc17 and 35S::AtDJC17. Localization of gene expression in the root using transgenic plants expressing pro:Atdjc17:GUS revealed constitutive expression in stele cells. No AtDJC17 expression was observed in epidermal, endodermal or cortical layers. To explore the contrast between gene expression in the stele and epidermal phenotype, hand cut transverse sections of Atdjc17 roots were examined showing that the endodermal and cortical cell layers displayed increased anticlinal cell divisions. Aberrant cortical cell division in Atdjc17 is proposed as causal in ectopic root hair formation via the positional cue requirement that exists between cortical and epidermal cell in hair cell fate determination. Results indicate a requirement for AtDJC17 in position dependent cell fate determination and illustrate an intriguing requirement for molecular co-chaperone activity during root development.